Studi Psikologi Pendidikan Berbasis Nilai-Nilai Al-Qur’an dalam Pembentukan Karakter Santri di Maahad Tahfiz Al-Qur’an Darul Falah Selangor - Miftahur Rahmah (PT. Hasba Edukasi Mandiri, 2025)
Character education based on the values of the Qur’an has become an urgent need in shaping the personality of students with noble character. The ongoing moral degradation highlights the importance of research and solutions to address this phenomenon. In the context of Islamic education, character is a fundamental element that not only reflects a student's personal quality but also serves as an indicator of the success of internalizing Islamic values derived from the Qur’an. This study aims to examine the implementation of Qur’anic values in educational psychology in the process of character formation among students at Maahad Tahfiz Al-Qur’an Darul Falah Selangor. This research employs a qualitative approach using a case study method, in which data were collected through observation and in-depth interviews. The findings reveal that the students’ character formation is achieved through the internalization of values such as faith, honesty, discipline, responsibility, and compassion rooted in the teachings of the Qur’an. These values are integrated into the learning process, daily routines, and modeled by the educators. The study concludes that the application of Qur’anic values in education at Maahad Tahfiz Al-Qur’an Darul Falah Selangor effectively fosters student character based on akhlaq al-karimah and strengthens their Islamic identity.